2016
DOI: 10.3892/or.2016.4564
|View full text |Cite
|
Sign up to set email alerts
|

SMC1 promotes epithelial-mesenchymal transition in triple-negative breast cancer through upregulating Brachyury

Abstract: Abstract. Triple-negative breast cancer (TNBC) is a special subtype of breast cancer, which is characterized by the negative form of estrogen receptor (ER), progesterone receptor (PR) and human epithelial growth factor receptor 2 (HER2). TNBC accounts for ~15% of all breast cancer forms, and often leads to high mortality and poor prognosis. Structural maintenance of chromosome 1 (SMC1) is a subunit of the cohesion protein complex. Brachyury is a protein that is encoded by the T gene in humans, which is a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Therefore, EMT makes tumor cells more invasive and resistant. Although in previous study, we have found that Brachyury can promote the occurrence of EMT of breast cancer cells [4,5], there is no clinical data supporting this. In this study, we prepared para n tissue from 303 cases of breast cancer tissues, constructed tissue chips, and tried to evaluate the value of Brachyury protein expression in breast cancer prognostic analysis using machine learning algorithms.…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, EMT makes tumor cells more invasive and resistant. Although in previous study, we have found that Brachyury can promote the occurrence of EMT of breast cancer cells [4,5], there is no clinical data supporting this. In this study, we prepared para n tissue from 303 cases of breast cancer tissues, constructed tissue chips, and tried to evaluate the value of Brachyury protein expression in breast cancer prognostic analysis using machine learning algorithms.…”
Section: Introductionmentioning
confidence: 62%
“…BRACHYURY/BRACHYURY is obviously highly expressed at the mRNA and protein levels in breast cancer tissues and cell lines compared to negativity in normal breast cancer tissues and cells (9,60,(63)(64)(65)(66). Hormone receptor status of breast cancer is an important and recognized prognostic factor and can reflect different stages (67), including estrogen receptor (ER) and progesterone receptor (PR).…”
Section: Breast Carcinomamentioning
confidence: 99%
“…Post-developmentally, brachyury is expressed in the testes and some thyroid tissues, but is undetectable in all other non-neoplastic adult tissues (Edwards et al, 1996; Hamilton et al, 2015). Interestingly, recent studies have reported the expression of brachyury in several epithelial cancers where it promotes growth, confers resistance to chemo- and radiotherapy, and drives epithelial-to-mesenchymal transition (EMT) (Cho et al, 2010; Fernando et al, 2010; Haro et al, 2013; Huang et al, 2013; Imajyo et al, 2012; Jezkova et al, 2016; Kobayashi et al, 2014; Larocca et al, 2013; Li et al, 2016; Miettinen et al, 2015; Palena et al, 2014; Park et al, 2008; Pinto et al, 2015; Pinto et al, 2014; Pires and Aaronson, 2014; Roselli et al, 2012; Sarkar et al, 2012; Shao et al, 2015; Shimoda et al, 2012; Vujovic et al, 2006; Xu et al, 2015; Yoshihama et al, 2016); however, the mechanistic details of how brachyury mediates these features of tumor progression have not been fully elucidated. Furthermore, the lack of brachyury expression in most adult non-neoplastic tissues and exclusive tumor-specific expression underscores its value as a potential diagnostic and therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 99%